New data of the Portuguese brachiosaurid Lusotitan atalaiensis (Sobral Formation, Upper Jurassic). (18th August 2017) - Mocho, P.; Royo-Torres, R.; Ortega, F.
Abstract: Lusotitan atalaiensis was one of the first sauropod taxa established for the Upper Jurassic of the Lusitanian Basin (Portugal). The lectotype of L. atalaiensis found in Peralta (Lourinhã) was firstly considered as new species of Brachiosaurus, considering the similarities with Brachiosaurus and Giraffatitan . This specimen was originally considered as a brachiosaurid, and more recently, a cladistics analysis, suggested Lusotitan as a basal macronarian and a possible member of Brachiosauridae. In this study, new information is provided about the Lusotitan lectotype, with reinterpretation and description of previously described and undescribed elements (e.g. sacral vertebrae, chevrons, ulna, ischium, pubis or fibula). The validity of this taxon is confirmed by a revised diagnosis. The present comparative study and the phylogenetic analyses suggest the assignation of Lusotitan to Brachiosauridae supported by the presence of pronounced and dorsoventrally short deltopectoral crest, short ischiatic contribution to the acetabulum and radius length/tibia length ratio >1. The presence of brachiosaurids in the Portuguese Upper Jurassic record is confirmed, supporting the presence of a wide paleobiogeographic distribution for Brachiosauridae during the Late Jurassic, being present in Europe, North America and Africa.